2021
DOI: 10.32517/0234-0453-2021-36-9-5-22
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the electronic educational resources accessibility on the university Moodle platform

Abstract: The purpose of the article is to assess the accessibility of electronic educational resources (EER) published in the university Moodle Learning Management System (LMS). The analysis involved 22 EERs in mathematical and information technology disciplines, located in the Moodle LMS of the V. I. Vernadsky Crimean Federal University. The examination algorithm included analysis using the Web Accessibility Evaluation Tool (WAVE) and expert analysis of web accessibility using visual, auditory and manual methods based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Meanwhile, respondent (R1) reported that the display on a laptop device was different from that on a smartphone so that at the beginning of learning process it was difficult for him to understand and navigate on Moodle LMS. (Kosova et al, 2021) reported an advantage of Moodle LMS especially regarding content reproduction errors on mobile devices.…”
Section: Assignment Notifications Didn't Exist On Moodle So Sometimes...mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, respondent (R1) reported that the display on a laptop device was different from that on a smartphone so that at the beginning of learning process it was difficult for him to understand and navigate on Moodle LMS. (Kosova et al, 2021) reported an advantage of Moodle LMS especially regarding content reproduction errors on mobile devices.…”
Section: Assignment Notifications Didn't Exist On Moodle So Sometimes...mentioning
confidence: 99%
“…In the use of Moodle LMS, several shortcomings were also reported such as lack of compatibility with text browsers, reproduction errors by screen readers, content reproduction errors on mobile devices (Kosova et al, 2021). The studies mentioned above, on average, used quantitative research as a research method, and therefore they provide space for quantitative research on the weaknesses of use of Moodle LMS in online learning during the Covid-19 Pandemic (Gamage et al, 2022) as in this study aims to examine using qualitative methods.…”
Section: Introductionmentioning
confidence: 99%